Culture, society and development in India: essays for Amiya Kumar Bagchi - Amiya Kumar Bagchi; Manoj Kumar Sanyal (ed.); Arunabha Ghosh (ed.) (New Delhi : Orient Blackswan, 2009)
Amiya Kumar Bagchi, b. 1936, Indian economist and historian; contributed articles.
Keywords: Cultural Pluralism; Multilingualism; Bengali language; Language and Culture; Women Literature; Popular Culture